THE EFFECT OF WATERPARK IMAGE THROUGH DELIGHT AND SERVICE QUALITY ON CUSTOMER LOYALTY - IRMA SATYA INDRIYANTI; FLORENSIA IRENE (Media Bisnis, 2020)
The purpose of this study was to examine and analyze the influence of waterpark image through delight and service quality to customer loyalty on Waterboom Lippo Cikarang customers in Jabodetabek. This research is a descriptive study and causal relationship. The sample in this study were 200 respondents. This research method is SEM analysis with Warp PLS tools. The results of this study indicate that waterpark image, delight, and service quality have a significant and positive influence on customer loyalty. Whereas indirectly waterpark image influences customer loyalty through delight and service quality.